The Influence of the Choice Of Majors on Student Interest in Learning at SMK Negeri 4 Kupang City - Sri Handani Ndolu; M. K. P Abdi Keraf; Yeni Damayanti (Journal of Health and Behavioral Science, 2021)
In general education is divided into two parts, namely formal education and non-formal education, which are both planned to create an atmosphere of learning and the learning process so that students can actively develop their potential. Formal education is education that is organized through institutionalized infrastructure such as schools, academics, universities. The success in undergoing this education at certain stages is symbolized by the provision of certificates. Meanwhile, non-formal education is a path of education outside formal education that can be implemented in a structured and tiered manner. The results of non-formal education can be valued as equal to the results of formal education programs after going through an equivalence assessment process by an institution appointed by the government or local government with reference to national education standards. The hypothesis in this study is there is an influence between the choice of majors on student interest in learning at SMK Ngeri 4 Kota Kupang. Participants in this study were students of class X, amounting to 100 respondents. The analysis in this study used multiple linear regression analysis. The results showed a positive and significant influence between the talent variable with a contribution of 15.9% and a significance value of 0.000 <0.05, the parent support variable with a contribution of 33.2% and a significance value of 0.000 <0.05, the peer variable on student interest in learning at SMK Negeri 4 Kota Kupang with a contribution of 16.0% and a significance value of 0.000 <0.05. Talent, Parental Support, Peers have a positive and significant effect jointly between the variables of talent, support from parents and peers on student interest in learning at SMK Negeri 4 Kota Kupang with a contribution of 33.3% and a significance value of 0.000 <0 , 05